Effects of Resistance Training on Immunoinflammatory Response, TNF-Alpha Gene Expression, and Body Composition in Elderly Women - Luís Ângelo Macêdo Santiago; Lídio Gonçalves Lima Neto; Guilherme Borges Pereira; Richard Diego Leite; Cristiano Texeira Mostarda; Janaina de Oliveira Brito Monzani; Wandson Rodrigues Sousa; Aruanã Joaquim Matheus Rodrigues Pinheiro; Francisco Navarro (Journal of Aging Research)
The aim of this study was to determine the effects of resistance training on the immunologic response, body composition, tumor necrosis factor-alpha (TNF-alpha) gene expression obtained from blood leukocytes, and the cytokines interleukin-6, TNF-alpha, and C-reactive protein (CRP), in the elderly women (mean age 63 ± 2 y). A randomized controlled trial was performed using a bi-set training method for eight weeks in nineteen elderly women. Peripheral blood samples were collected by puncture in pretraining (Pre) and posttraining (Post) moments. In the resistance training group, there was a statistically significant decrease from 38.43 ± 9.48 pg/mL to 11.76 ± 5.19 pg/mL (p=0.01) in the serum levels of interleukin-6. Considering serum levels of TNF-alpha, there was a statistically significant difference, comparing the resistance training group at Pre (66.27 ± 10.31 pg/mL) and Post (37.85 ± 9.05 pg/mL) moments (p=0.01). In molecular analysis of TNF-alpha gene expression, there was a statistically significant decrease (p=0.007) between Pre (0.010 ± 0.01 ng/ml) and Post (0.0002 ± 0.0001 ng/ml) moments. Among CRP data, in the resistance training group, there was a statistically significant reduction, between Pre (2.04 ± 0.32 mg/L) and Post (0.90 ± 0.22 mg/L) moments (p=0.001). In the Control group, there was no statistical significance between these two moments. Therefore, the resistance training demonstrated changes in the TNF-alpha gene expression in elderly women, as well as decreased serum levels of interleukin-6, TNF-alpha, and CRP. Such conditions may be related to immune modulation and anti-inflammatory effects, since resistance training releases cytokines, especially interleukin-6, which acts as a TNF-alpha antagonist during exercise.